Manajemen Penguatan Karakter Santri - Muhammad Mujtabarrizza; Siminto Siminto; Muslimah Muslimah (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
Character education is a system of cultivating the character of knowledge, awareness or will, and actions to implement these values. Islamic boarding schools as non-formal educational institutions are spaces for preparing students in terms of needing large and quality human resources to support the implementation of development programs properly. The quality education, which can support the achievement of the nation's ideals in having quality resources. This study aims to determine the extent to which management strengthens the character of students in Islamic boarding schools. Data were analyzed using a qualitative-descriptive approach with the literature review method. So as to produce findings that the principles of Islamic boarding schools in an effort to strengthen the character of students are through theocentric principles, voluntary, wisdom, simplicity, collectivity, organizing joint activities, ukhuwah, and freedom.